The Effect of Pandan Leaf Decoction on Reducing Blood Glucose Levels among Patients with Diabetes Mellitus in RT 02 RW 04 Kampung Sukamanah, Parung Panjang, Bogor - Achirman Achirman; Gaung Eka Ramadhan; Tati Suryati; Luthfia Rahmi (Asosiasi Dosen Muda Indonesia, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels and may lead to serious complications if not properly controlled. The use of accessible herbal-based complementary therapies, such as pandan leaf decoction, has become an alternative approach to support blood glucose management in the community. Objective: This study aimed to determine the effect of pandan leaf decoction on reducing blood glucose levels among patients with diabetes mellitus in RT 02 RW 04 Kampung Sukamanah, Parung Panjang, Bogor. Method: This study employed a quantitative quasi-experimental design using a one-group pretest-posttest approach. A total of 18 respondents were selected through purposive sampling. Data were collected by measuring fasting blood glucose levels before and after the administration of 200 ml pandan leaf decoction once daily for five consecutive days. Data were analyzed using univariate analysis and the paired sample t-test. Findings: The results showed that the mean fasting blood glucose level decreased from 279.61 mg/dL before the intervention to 153.78 mg/dL after the intervention. Statistical analysis revealed a significant difference between pretest and posttest measurements, with a p-value of 0.001, indicating that pandan leaf decoction was associated with a significant reduction in blood glucose levels among patients with diabetes mellitus. Implications: The findings suggest that pandan leaf decoction may be utilized as an affordable and accessible complementary non-pharmacological intervention to support blood glucose control in community-based diabetes management programs. The results may also serve as a reference for nursing practice and public health promotion related to complementary therapies. Originality: The originality of this study lies in providing empirical evidence from a community setting regarding the potential use of pandan leaf decoction as a complementary herbal intervention for reducing blood glucose levels among patients with diabetes mellitus. This study contributes practical knowledge on the utilization of local herbal resources in supporting diabetes management.